Efektivitas Pembelajaran Daring, SwayVS Form SD Negeri Kedunggubah - Retno Suprihartini; Victor Novianto (UM Purwokerto Press, 2022)
The development of education today is influenced by the rapid progress of information and communication technology. One of the information technologies that play a role in the world of education is online learning. Online learning functions as a liaison between educators and students with an internetnet work that can be accessed anytime and anywhere. The online media used by the research subjects were various (Sway,Form). The purpose of this study is to identify online learning activities at the homes of students as an effort to support government programs, namely study from home during the Covid 19 pandemic and to analyze the effectiveness of online learning. The method used in data collection was a question and answer session to sources,namely primary school teachers through interviews. The results showed that online learning that was carried out at home made students more independent and created motivation to learn. Inaddition, online learning is one of the successes in creating social distancing behavior soas to minimize the appearance of crowds which are considered to have the potential to spread Covid19 in the school environment. However, it is still ineffective in its implementation due to various obstacles such as economic capability, mastery of technology, internet quota, and inadequate network.